2019
DOI: 10.1167/19.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and oculomotor evidence for visual simulation of object movement

Abstract: We regularly interact with moving objects in our environment. Yet, little is known about how we extrapolate the future movements of visually perceived objects. One possibility is that movements are experienced by a mental visual simulation, allowing one to internally picture an object's upcoming motion trajectory, even as the object itself remains stationary. Here we examined this possibility by asking human participants to make judgments about the future position of a falling ball on an obstacle-filled displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Further, we showed that participants' reaction times were greater and accuracy was lower on high simulation uncertainty boards relative to low simulation uncertainty boards. (Ahuja & Sheinberg, 2019). Here, we sought to replicate these effects from our past experiments to verify that participants' behavior on the task matched what we have previously presented as evidence in favor of simulation.…”
Section: Behavioral Analysesmentioning
confidence: 64%
See 2 more Smart Citations
“…Further, we showed that participants' reaction times were greater and accuracy was lower on high simulation uncertainty boards relative to low simulation uncertainty boards. (Ahuja & Sheinberg, 2019). Here, we sought to replicate these effects from our past experiments to verify that participants' behavior on the task matched what we have previously presented as evidence in favor of simulation.…”
Section: Behavioral Analysesmentioning
confidence: 64%
“…An example of a low simulation uncertainty board is shown in Figure 2C. A dynamic demonstration of these uncertainty categories is shown in a supplementary video from our previous paper (Ahuja & Sheinberg, 2019). Simulation length and simulation uncertainty categories were counterbalanced, leading to six trials per length and uncertainty combination per block (2 length categories X 2 uncertainty categories X 6 = 24 trials).…”
Section: Classification Of Boardsmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in this figure, participants were generally very good at all three task variants and performed far better than chance, which was defined as 50% correct (Simulation: 89.8%, [t 11 = 39.745, p < 0.001]; Perception: 99.6% [t 11 = 199.23, p < 0.001]; Control: 99.4% [t 11 = 155.45, p < 0.001]). Previously, we showed that people perform the ball fall task via simulation by relating their reaction times and accuracy to two simulation-based metrics – length and uncertainty (Ahuja & Sheinberg, 2019). Specifically, we showed that as simulation length increased, so did participants’ reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…Eye-tracking in particular has proven a promising approach. In a variety of intuitive physical tasks, researchers have captured human eye-data to investigate claims about mental simulation (Ahuja & Sheinberg, 2019;Crespi, Robino, Silva, & de'Sperati, 2012;Gerstenberg, Peterson, Goodman, Lagnado, & Tenenbaum, 2017). Eye-data yield a moment-to-moment trace of human behavior throughout the process of making a physical judgment, augmenting standard behavioral measures and providing rich empirical fodder for making inferences about human cognition.…”
Section: Introductionmentioning
confidence: 99%